MENINGKATKAN HASIL BELAJAR MATERI KOORDINAT MATA PELAJARAN MATEMATIKA MELALUI STRATEGI CRITICAL INCIDENT PADA SISWA KELAS VI MADRASAH IBTIDAIYAH NEGERI PEMBANTANAN SUNGAI TABUK KABUPATEN BANJAR - Bashith, Abdul (Journal of Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2015)
This research aims to improve student learning outcomes in class VIA the second semester of academic year 2013-2014 at MIN Pembantanan, Sungai Tabuk, Banjar Regency, in mathematics by using active learning model type of critical incident. This classroom action research conducted in two cycles. At each cycle, the cycle 1 and cycle 2 consists of two meetings with 2x35 minute time allocation. The subjects of this study were students VIA MIN Pembantanan, Sungai Tabuk, Banjar Regency, second semester of academic year 2013-2014, the number of subjects are 28 students, which are 15 men and 13 women. Data in this study were obtained through observation and written tests, while data analysis technique used is the average and percentage. The results were obtained (1) Implementation of the learning with the application of learning strategies in the learning of mathematics critical incident coordinates material in class VIA MIN Pembantanan, Sungai Tabuk, Banjar Regency, runs well and maximum. The quality of learning is increasing based on teaching-learning activities increased with the percentage of 73.9% in the first meeting and the second meeting 82.6%. At the first meeting of the second cycle is 95.6% and in the second meeting reaches 100%. Overall average percentage of the teacher’s teaching process included in the “Very Good” category; (2) Activity of students in the percentage increased from 68% in the first meeting to 72% in the second meeting. At the first meeting of the second cycle is 86% to 96% at the second meeting; (3) The results of student learning increased with the implementation of learning strategies critical incident on the material “coordinate”, it can be seen on student learning outcomes in the first cycle, the average value at the first meeting is 50.7, and the second meeting is 57.14. Then in the second cycle at the first meeting and the second meeting are 69.6 and 76.78. Thus the critical incident learning strategies in mathematics learning of coordinate materials can be said to be successful because of the results achieved already meet that target thoroughness in learning mastery learning value of 56.00.